The Centrality of Christ in the Epistle to the Hebrews: Theological Themes and Their Importance for the Present Day Church - Budiman, Sabda; Luthy, Christopher James; Wijaya, Hengki (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
In a number of ways, the epistle to the Hebrews is a unique letter among the New Testament epistles because of its Jewish nuance and emphasis on the Mosaic Covenant. The author quotes and alludes to Old Testament texts in a variety of ways, which has aroused great interest for many theologians. The theological themes of the letter have also resulted in much study, particularly when one attempts to apply these unique themes to the present-day church. This study focuses on six of these themes (God, Christ, Priest, Covenant, Endurance, and Faith) and their significance for the current church contexts. A text analysis research method is employed to exegete various texts. In accordance with many other studies on the subject, this study also concludes that the epistle to the Hebrews is profoundly Christocentric. Christ is the primary focus in all the letter’s emphases. The writer of Hebrews seeks to explain the superiority of the New Covenant, and how the Old Testament was ultimately focused on and fulfilment through Christ.